ความคิดเห็นของลูกค้าต่อการจัดการลูกค้าสัมพันธ์ของ ธนาคารกรุงไทยสาขาเชียงดาว - ธีรยุทธ สายศรีธิ (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2018)
The purpose of this independent study was to study opinion of customers towards customer relationship management of Krung Thai Bank Public Company Limited, Chiang Dao Branch. The questionnaire was used to collect data, and descriptive statistics as frequency, percentage and mean were used to analyze the data. The study revealed that the respondents were women, age between 21 – 30 years, educated at bachelor degree level with a salary between 10,001 to 20,000 Baht, and were employed by the government or state enterprises. Most of the respondents chose the service of Krung Thai Bank Public Company Limited, Chiang Dao Branch regarding deposit-withdrawal for more than 3 years. The reasons for choosing Krung Thai Bank Public Company Limited, Chiang Dao Branch was because of the location that was convenient and located near home and workplace. The respondents’ opinions toward customer relationship service of Krung Thai Bank Public Company Limited, Chiang Dao Branch regarding sales force automation was in agree level. The first sub-factors from the opinion’s average in each factors were as followed: In the opportunity factor was the bank had personal record of customers regarding financial transaction such as purchasing product or service, asking for loans, using credit cards or deposit the money; In lead management factor was the counter staff who would forward the issue to supervisor in order to the customers later on; In the tracking factor was the staff who would record any questions of the costumers in order to analyze and answer the costumers clearly; In the order fulfillment was dealing with orders from the costumers immediately once the costumers accepted the agreement; In the sale processes factor was sending the remote system to customers such as SMS alert, calling, or sending information through E-mail; In the follow-up opportunity factor was giving products, souvenirs, or special services to all important customers.